Правова природа висновку і показань експерта-психіатра - Макарова, О. П.; Makarova, O. P. (Наше право. - 2024. - № 1. - С. 119-124, 2024)
Розглянуто правову природу висновку і показань експерта-психіатра в кримінальних провадженнях. Досліджено поняття, структура та зміст висновку експерта-психіатра, а також його доказове значення. Зазначено, що висновок експерта-психіатра є процесуальним документом, який складається експертом-психіатром на підставі проведеного ним дослідження. Висновок є джерелом доказів у кримінальному провадженні та має значення для встановлення всіх обставин, які мають значення для кримінальної відповідальності.

The article examines the legal nature of the opinion and testimony of a psychiatric expert in criminal proceedings. The concept, structure and content of the expert psychiatrist’s opinion, as well as its evidentiary value are investigated. The author notes that the conclusion of a psychiatric expert is a procedural document drawn up by a psychiatric expert on the basis of his/her research. The conclusion is a source of evidence in criminal proceedings and is important for establishing all the circumstances relevant to criminal liability. The testimony of a psychiatric expert is factual information that he or she provides to a court or other body conducting criminal proceedings during interrogation. They are also a source of evidence in criminal proceedings and are important for establishing all the circumstances of the case that are relevant to criminal liability. It is noted that the conclusions and testimony of a psychiatric expert are of particular importance in criminal proceedings, since they relate to the mental state of a person who is an accused, victim, witness or suspect. These conclusions and testimony can be crucial for deciding on the criminal liability of a person, as well as for imposing punishment or medical measures. The article also addresses the issues of admissibility of expert psychiatric opinion and testimony in criminal proceedings. The author notes that these conclusions and testimony must be admissible, i.e. they must meet the requirements of criminal procedure legislation. The author concludes that the opinion and testimony of a psychiatric expert is an important source of evidence in criminal proceedings. They are of particular importance for establishing the mental state of a person who is a party to criminal proceedings and may be crucial for deciding on his or her criminal liability.

Рассмотрена правовая природа заключения и показаний эксперта-психиатра в уголовных производствах. Исследованы понятие, структура и содержание заключения эксперта-психиатра, а также его доказательное значение. Отмечено, что заключение эксперта-психиатра является процессуальным документом, составляемым экспертом-психиатром на основании проведенного им исследования. Вывод является источником доказательств в уголовном производстве и имеет значение для установления всех обстоятельств, имеющих значение для уголовной ответственности.
Legal nature of the conclusion and testimony of a psychiatric expert
Keywords: висновок; експерт – психіатр; кримінальне провадження; докази; показання; opinion; expert psychiatrist; criminal proceedings; evidence; testimony; заключение; эксперт – психиатр; уголовное производство; доказательства; показания